The Principle of People's Authoritative Manifestation in Mining Management: An Inclusive Legal Perspective - Taufiq, Muchamad; Disantara, Fradhana Putra (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Principle of the people's authoritative manifestation in mining activities must be a reference and guide by the state in formulating policies related to mining management.Purposes of the Research: This study aims to construct the people's authoritative manifestation principle in mining management. In addition, this study also focuses on an inclusive legal perspective and uses comparisons with Brazil and the United States.Methods of the Research: This research is normative legal research with the approaches used conceptual, comparative, and statutory approaches.Results of the Research: The study results confirm that the efforts to actualize the principle of authoritative manifestation of the people in an inclusive legal perspective can be carried out with an integrated mining licensing system that takes into account the aspirations and input of the community, the need for community participation and involvement in every mining management activity, and the need for protection and empowerment, especially for communities around mining and in particular again to customary law communities who have local wisdom to manage local resources in their area so that their existence is maintained even though there is mining activity.